1997
DOI: 10.1016/s0022-5347(01)64799-2
|View full text |Cite
|
Sign up to set email alerts
|

Tubeless Percutaneous Renal Surgery

Abstract: Tubeless percutaneous renal surgery is a safe procedure and offers numerous advantages over routine placement of a nephrostomy tube. The hospitalization, analgesia requirements, return to normal activities as well as cost are significantly less with this new technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
168
1
9

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 318 publications
(187 citation statements)
references
References 10 publications
2
168
1
9
Order By: Relevance
“…Several new techniques of PCNL such as mini-PCNL and tubeless PCNL were reported to decrease morbidity, analgesic requirement and duration of hospitalization (7). The method of anesthesia was reported to minimize morbidity following PCNL.…”
Section: Resultsmentioning
confidence: 99%
“…Several new techniques of PCNL such as mini-PCNL and tubeless PCNL were reported to decrease morbidity, analgesic requirement and duration of hospitalization (7). The method of anesthesia was reported to minimize morbidity following PCNL.…”
Section: Resultsmentioning
confidence: 99%
“…18 Bellman et al describe the advantages of placement of nephrostomy tube after PCNL and demonstrated that the haemostatic process was easy, it provide an access if second look procedure is required and prevent urinary extravasation. 19 Tubeless PCNL was found by Falahatkaret al on 42 renal units for staghorn stones, they found that the procedure is safe and effective even with less complications. 20 The major concern in PCNL surgery involves serious postoperative complications such as blood loss, adjacent organ injuries and life threatening infection.…”
Section: Discussionmentioning
confidence: 97%
“…15 There have been significant advances in the percutaneous extraction of renal calculi. [2][3][4][5][6][7][8][9][10] Review articles have highlighted the need for minimal intra-operative bleeding, negligible residual stone burden, and one to two attempts at renal access when considering tubeless approaches. Recently, the ability to perform tubeless PCNL as an outpatient procedure has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Since its description in the 1970s, 1 surgical and technological advances have obviated the need for routine nephrostomy tube placement. [2][3][4][5][6][7][8] Tubeless PCNL, with ureteral stenting, has been shown to decrease patients' analgesic requirements and hospital length of stay. 9,10 Although hospitalization is standard practice after PCNL, reports have described success with outpatient management.…”
Section: Introductionmentioning
confidence: 99%